Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
Solution :-
i) Given expressions are 2a + b, a + b
On Subtracting second expression form the first expression
=> (2a+b) -(a+b)
=> 2a+b-a-b
=> (2a-a)+(b-b)
=> a+0
=> a
ii) Given expressions are - 2b + 2c, b + 3c
On Subtracting second expression form the first expression
=> (- 2b + 2c)-( b + 3c)
=> -2b+2c-b-3c
=> (-2b-b)+(2c-3c)
=> -3b-c
iii) Given expressions are 5a + b, - 6b + 2a
On Subtracting second expression form the first expression
=> (5a + b)-(- 6b + 2a )
=> 5a+b+6b-2a
=> (5a-2a)+(b+6b)
=> 3a+7b
iv) Given expressions are a³-1+a, 3a-2a²
On Subtracting second expression form the first expression
=> (a³-1+a)-(3a-2a²)
=> a³-1+a-3a+2a²
=> a³-1-2a+2a²
=> a³+2a²-2a+1
v) Given expressions are p + 2,1
On Subtracting second expression form the first expression
=> (p+2)-(1 )
=> p+2-1
=> p+1
vi) Given expressions are x + 2y + z , -x - y - 3z
On Subtracting second expression form the first expression
=> (x + 2y + z )-(-x - y - 3z )
=> x+2y+z+x+y+3z
=> (x+x)+(2y+y)+(z+3z)
=> 2x+3y+4z
vii) Given expressions are 3a²-8ab-2b²,3a²-4ab+6b²
On Subtracting second expression form the first expression
=> (3a²-8ab-2b²)-(3a²-4ab+6b²)
=> 3a²-8ab-2b²-3a²+4ab-6b²
=> (3a²-3a²)+(-8ab+4ab)+(-2b²-6b²)
=> 0+(-4ab)+(-8b²)
=> -4ab-8b²
viii) Given expressions are 4pq-6p²-2q²,9p²
On Subtracting second expression form the first expression
=> (4pq-6p²-2q²)-(9p²)
=> 4pq-6p²-2q²-9p²
=> 4pq-15p²-2q²
ix) Given expressions are 10abc,2a²+2abc-4b²
On Subtracting second expression form the first expression
=> (10abc)-(2a²+2abc-4b²)
=> 10abc-2a²-2abc+4b²
=> 8abc-2a²+4b²
x) Given expressions are a²+ab+c², a²-d²
On Subtracting second expression form the first expression
=> (a²+ab+c²)-( a²-d²)
=> a²+ab+c²-a²+d²
=> (a²-a²)+ab+c²+d²
=> 0+ab+c²+d²
=> ab+c²+d²
Hope this helps!!
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.